2021
DOI: 10.1155/2021/6639017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Parasitological, and Serological Follow-Up of Dogs with Sarcoptic Mange Treated Orally with Lotilaner

Abstract: Canine sarcoptic mange is a highly pruritic and contagious skin disease caused by the mite Sarcoptes scabiei var. canis. This case series describes the clinical, parasitological, and serological follow-up of a cohort of eight adult Saint Bernard dogs with confirmed sarcoptic mange, treated orally with lotilaner. Dogs were evaluated initially and after 14 days and 1, 2, 3, 4, 6, and 12 months for skin lesions, pruritus severity, presence of parasites, and Sarcoptes-IgG levels. A serological indoor allergy panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Treatment options for sarcoptic mange includes fipronil, ivermectin, selamectin, milbemycin and moxidectin/imidacloprid 19–26 . More recently the isoxazoline class of drugs, including fluralaner, afoxolaner, sarolaner and lotilaner, has been shown to be efficacious against S. scabiei when used topically and orally 27–31 . In the present case, the dog was treated with a single dose of oral fluralaner and achieved complete resolution one month after administration.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Treatment options for sarcoptic mange includes fipronil, ivermectin, selamectin, milbemycin and moxidectin/imidacloprid 19–26 . More recently the isoxazoline class of drugs, including fluralaner, afoxolaner, sarolaner and lotilaner, has been shown to be efficacious against S. scabiei when used topically and orally 27–31 . In the present case, the dog was treated with a single dose of oral fluralaner and achieved complete resolution one month after administration.…”
Section: Discussionmentioning
confidence: 67%
“…[19][20][21][22][23][24][25][26] More recently the isoxazoline class of drugs, including fluralaner, afoxolaner, sarolaner and lotilaner, has been shown to be efficacious against S. scabiei when used topically and orally. [27][28][29][30][31] In the present case, the dog was treated with a single dose of oral fluralaner and achieved complete resolution one month after administration. To the authors' knowledge, this is the first report of treatment of crusted sarcoptic mange in a canine with an isoxazoline.…”
Section: Discussionmentioning
confidence: 74%
“…Due to the similar clinical and parasitological efficacy of these substances, comparative studies using a similar design are now needed to identify the most efficient product. Previous studies have been demonstrated that clinical healing and absence of parasites at skin scrapings occur weeks to months before obtaining negative serum Sarcoptes -IgG tests [ 5 ]. However, adding to the classical evaluation methods a long-term serological surveillance might add new useful data and provide for clinicians a complete data set for tested molecules.…”
Section: Conclusion and Implication For Practitionersmentioning
confidence: 99%
“…The disease is often complicated by secondary pyoderma, which determines the extent of the lesions and contributes to the diversity of clinical presentation, ultimately complicating the diagnosis [ 2 , 4 ]. Hypothetical diagnoses are based on the clinical presentation [ 1 ], while confirmation is obtained by demonstrating the presence of the parasite, its eggs or fecal pellets in skin scrapings [ 2 ] or positive serology [ 3 ] or a favorable response to a specific therapy [ 2 , 5 ]. The diagnosis of sarcoptic mange may be complicated by several factors: the mites are difficult to find by skin scraping in early infections and in animals harboring low levels of parasitism, and therefore only 20 – 50% of skin scrapings from infested dogs are positive [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…55 Apart from possible differences in the immune response generated in different hosts, inconsistency in data obtained from human subjects and animals with scabies may be because of low sensitivity of the antibody-detection methods used, as a result of crossreactivity of anti-scabies antibodies with house dust mite and host antigens. [91][92][93][94][95][96][97] Serologic reactivities to different S. scabiei mite antigens also showed differences depending on the clinical form of sarcoptic mange, 78,98 as well as between primary and secondary infestations. 85 Additionally, intrinsic factors such as sex and age were also observed to influence antibody levels produced in response to scabies.…”
Section: Humoral Responsementioning
confidence: 99%